A global prediction of cardiovascular disease from 2020 to 2030 - Huiqun Yang; Huiqun Yang; Huiqun Yang; Qinghua Ma; Liyuan Han; Liyuan Han; Liyuan Han; Huina Liu; Huina Liu; Huina Liu (Frontiers in Cardiovascular Medicine)
BackgroundThe study aimed to forecast the incidence, mortality, and disability-adjusted life years (DALY) related to cardiovascular disease (CVD) across all age groups worldwide from 2020 to 2030.MethodsData spanning from 1990 to 2019 across diverse global populations were extracted from the GBD 2019 study data. Generalized Additive Models (GAM) were utilized to predict the disease burden for the period between 2020 and 2030. The estimated annual percentage change (EAPC) was employed to measure the temporal trends.ResultsThe EAPC for age-standardized incidence rate (ASIR) is projected to be 0.11 from 2020 to 2030, while for age-standardized death rate (ASDR) it is expected to be −1.11, and for age-standardized DALY rate it is estimated to be −1.04. By 2030, males are predicted to experience a higher burden compared to females, with higher ASIR (5,092.65 vs. 3,553.02) and ASDR (245.92 vs. 184.33), as well as a higher age-standardized DALY rate (734.72 vs. 653.71). Oceania is anticipated to have the highest age-standardized DALY rate at 9,556.79. Central Asia stands out among the regions with the highest ASIR (437.48) and ASDR (1,093.93). Lower Socio-Demographic Index (SDI) regions are projected to bear a greater burden of CVD by 2030, indicating an inverse relationship between SDI and CVD burden. Cabo Verde leads with the highest EAPC for DALYs and deaths at 4.08 (95% CI: 3.93, 4.23) and 4.82 (95% CI: 4.61, 5.04), respectively. The highest EAPC for incidence is observed in Slovenia at 1.80 (95% CI: 1.78, 1.83).ConclusionFrom 2020 to 2030, the global CVD burden is projected to rise, with males and low SDI regions—particularly Oceania, Central Asia, and Cabo Verde—facing the highest risks. Strengthening primary prevention (e.g., addressing diet, physical inactivity, tobacco), implementing gender-specific interventions, and improving healthcare access in low-SDI areas are critical. Global collaboration and targeted investments can mitigate disparities and reduce preventable deaths, aligning with equitable health outcomes.